The Relationship Between Service Quality and Outpatient Repeat Visit Interest at the Integrated Service Unit of Adi Husada Kapasari Hospital - Saputra, Reinaldo Dwiki; Hermanto Wijaya; Afif Kurniawan; Yura Witsqa Firmansyah (Asosiasi Dosen Muda Indonesia, 2025)
The quality of hospital services is an important factor that influences patient perception, satisfaction, and loyalty. This study aims to analyze the relationship between service quality and the interest of outpatients in revisiting the Integrated Service Unit at Adi Husada Kapasari Hospital. This quantitative cross-sectional study involved 68 respondents selected through purposive sampling from a population of 6,155 patients during the period March–June 2025. Service quality was measured using six dimensions: safe, effective, patient-centered, timely, efficient, and equitable. The interest in revisiting was measured based on the willingness of patients to return to use the services. Data analysis was performed using Spearman's rho correlation test. The results showed that all dimensions of service quality were in the good category, with the highest scores in the safe, efficient, and equitable dimensions (94.1%) and the lowest in the effective dimension (83.8%). Patient interest in return visits was very high, with 98.5% of respondents expressing interest in returning for treatment. However, the correlation test showed no significant relationship between service quality and interest in return visits (r = –0.026; p = 0.832). These findings indicate that even though service quality is high, other factors beyond service quality, such as location, cost, promotion, and third-party recommendations, are likely to have a greater influence on patients' decisions to return. Further research is recommended to explore other variables that may influence patients' interest in revisiting.